تشتت الانتباه وفرط الحركة لدى تلاميذ المرحلة الابتدائية من وجهة نظر معلميهم - حابي, حليمة; ممادي, شوقي (جامعة الوادي - University of Eloued, 2021)
الملخص: تهدف الدراسة الحالية إلى الكشف عن نسبة انتشار اضطراب تشتت الانتباه وفرط الحركة لدى عينة من تلاميذ المرحلة الابتدائية من وجهة نظر معلميهم، والكشف عن درجة الفروق فيها تبعاً للجنس. وقد اتبعت الدراسة المنهج الوصفي. تكونت العينة من (55) تلميذا وتلميذة من تلاميذ الصفين الثالث والرابع ابتدائي بمدينة الوادي، اختيروا بطريقة قصدية من بين (552) تلميذ، ولتحقيق أهداف الدراسة تم استخدام معايير لتشخيص اضطراب ومقياس تقدير المعلم لتشتت الانتباه وفرط الحركة من إعداد (ممادي، 2013). أظهرت النتائج أن نسبة التلاميذ من ذوي اضطراب كما بينت النتائج على أن نسبة انتشار هذا الاضطراب بين الذكور تفوق نسبة انتشاره لدى الإناث. تمت مناقشة النتائج في ضوء الإطار النظري وأوصت الدراسة بضرورة التدخل المبكر وتقديم الخدمات اللازمة لهؤلاء الفئة للحد من تفاقم هذه المشكلة. Abstract: The present study aims to detect the prevalence of Attention distraction and hyperactivity disorder (ADHD) among a sample of primary school students from the viewpoint of their teachers, and to reveal the degree of differences in them according to gender. The study followed the descriptive approach. The sample consisted of (55) students from the third and fourth grades of primary school in El-Oued. These students were chosen intentionally from a total of (552) student. To achieve the goals of the study, DSM-5 criteria were used to diagnose ADHD and the teacher’s measure of distraction and hyperactivity prepared by (Mammadi, 2013). The results, discussed in the light of the theoretical framework, showed that the percentage of students with (ADHD) was (5.60%) out of (552). they also showed that the prevalence of this disorder among males exceeds that of females. The study recommended the necessity of early intervention and providing the necessary services to this group to reduce the exacerbation of this problem.
مقال
Keywords: اضطراب تشتت الانتباه وفرط الحركة؛ تلاميذ المرحلة الابتدائية؛ المعلمين; Attention distraction and hyperactivity disorder; primary school student; teachers.